Common Sense and the Humanistic Perspective - Mungaray Lagarda, Ana Marcela; Núñez Villavicencio, Herminio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
This paper discusses the concept of common sense in the humanism. We´ll consider two proposals for the discussion on this concept: On the one hand, the classical conception of humanism considered in crisis associated with a lack of pluralism and inclusion from the ordinary to the contents and humanistic practice. On the other hand, the idea about that common sense in the context of the humanism is heterogeneous, so it recreates and includes in a new dialogue the everyday man by himself. The invitation from the United Nations about “Humanism, a new idea” (2011) is the context like a great call to refocus the discussion on practices derived from humanistic policy agreements in the world, integration projects between the classical traditions of the concept and dreams of interdisciplinary integration in the concert of nations. The path of analysis on the concept about the common sense in this proposal is a guide to review the rational framework as a concept in crisis. This is considering from several interpretations in a dialogic discussion, both the diversity debate about the nature of the concept as the depth of the social implications of the proposals.